The vocabulary of the Septuagint and its Hellenistic background - Bons, Eberhard; Pouchelle, Patrick; Scialabba, Daniela (Wissenschaftliche Untersuchungen zum Neuen Testament, 2019)
Introduction / Eberhard Bons, Patrick Pouchelle, Daniela Scialabba -- Le vocabulaire de la Septante à la lumière des papyrus / Anna Passoni Dell'Acqua -- Die Blöße der Stadt-Frauen: Überlegungen zur Verwendung der Substantive [aischunē] und άσχημοσύνη [aschēmosunē] in der Septuaginta / Nesina Grütter -- La main de Cyrus ou la main de Dieu?: Étude de l'expression [apostellō tēn cheira] dans la Septante / Patrick Pouchelle -- Coining Silver: The Translation of [keseph] in the Septuagint / Justus T. Ghormley -- Why is God not designated as an [archōn] in the Septuagint? / Marieke Dhont -- [Houtos de ouden atopon epraksen] (Luke 23:41): What Did the Good Thief Want to Say? A New Testament Citation and its Papyrological Background / Daniela Scialabba -- Nuances of Meaning with Compound Words in the Septuagint: A Case Study of [diagonguzō] and [eisakouō] in Contexts of Grumbling / David S. Hasselbrook -- Die Übersetzung [para tas dieksodous tōn hudatōn] in Psalm 1,3 und ihr griechischer Hintergrund / Eberhard Bons -- The Semantic Evolution of the Word [parrēsia] through its Pragmatic and Sociolinguistic Fields / Kyriakoula Papademetriou -- [Paradeisos] and [kēpos]: Thoughts about the Garden Terminology of the Septuagint / Beatrice Perego -- The Verb[sunantilambanomai]: The History of a New Compound Created in the Hellenistic Epoch / Miriam Carminati.